Organization and functioning of kindergartens managed by the Caritas Catholic Association - regional division in Kielce in 1950-1960 - Małgorzata Stawiak-Ososińska; Sylwia Gołuch (Maria Curie-Skłodowska University, Lublin, Poland, 2020)
After the end of World War II, in 1950, the Caritas division, established as a Catholic organization, was converted into a lay institution governed by the Caritas Catholic Association, a communist body. The activity of this new formation was focused on helping those in need and on providing aid to the poorest. The division took over Caritas' entire property. Among the facilities now governed by the institution were kindergartens. In Kielce itself, there were 21 kindergartens managed by the Association. The article presents the resources of particular facilities governed by the Caritas Catholic Association, the principles of their functioning, the methods of work with the wards, and the scale of care provided to pre-schoolers in the then Kieleckie Voivodeship.